Áreas de preservação permanente no entorno do Parque Nacional do Caparaó, no estado do Espírito Santo - Chimalli, Tessa (2013)
The current study aimed to analyze the changes induced by the amendment of Brazilian Forest Code (FC) in Permanent Preservation Areas (PPA) in the surroundings of the National Park of Caparaó. This research also aimed to evaluate the influence of the relief on the conservation of these areas. In order to map the preservation areas of nascent and watercourse it was used a hydrography achieved by means of photointerpretation in screen of aerial photos of the region. The photos were also used to map all forest fragments above 0.5 ha. We mapped five classes of APP’s. During the mapping of the PPA of hillsides with slopes higher than 45 degrees, hilltops and mountains and altitude of 1800 meters above, we have generated the Digital Elevation Model Hydrologically Consistent (DEMHC) from level curves with vertical equidistance of 20 m and spatial resolution of 10 m. Subsequently, we applied the chisquared test on the combinations of the dot matrix images of PPA considering the categories of relief altitude, steepness and aspect. Through the results we verified that the changing of the Forest Code induced a reduction of 6.44% of the PPA in 65,238.84 ha in the studied area and increased the percentage of PPA preserved from 17% to 18.3%. All classes of PPA became 24.8% of the studied area, being the more expressive class located in hilltops and mountains and they represented 76.19% of the PPA in the old FC and 69.62% in the new FC. In the new FC the municipalities that contribute to preservation areas with forests are Iúna (23.3%) and Irupi (20.3%), and those that are most in need of legal suit are Ibatiba (9.9%) and Ibitirama (14.8%). The presence of forest cover was significantly related to the altitude. Classes of PPA of watercourse and hilltops and mountains are more impacted between 495.52 m and 1, 110.44 m. Classes of steepness from plan-relief (0.3°) to strong topographic places (20- 45°) were also substantial for these same classes of PPA, as well as the mountainous relief (45-75°) for hilltops and mountains. All orientations of the sides were significant for the conservation status of the PPA, and the southern,the southeast and the southwest sides show the less impacted PPA. The use of geoprocessing and analysis of the influence of relief on the conservation status of the PPA were effective and contributed to future decision-making actions that aim the conservation of biodiversity and law enforcement.